Potential economic variables and actual economic policies in Europe - Erik Klär (Intereconomics, 2013)
Ignoring for a moment the debate on whether balanced budget rules are a sensible idea from a macroeconomic point of view, there remains a major problem with tying one's fi scal policy to econometric estimates of potential variables: their notorious unreliability. With every one of its biannual economic forecasts, the EC provides revised estimates of structural parameters that are crucial components of its macroeconometric models and, by extension, its economic policy advice. This article shows that the EC's econometric estimates of potential growth variables in Europe have been subject to massive revisions since the financial crisis.
Keywords: 330; Wirtschaftspolitik; Wirkungsanalyse; Konjunkturprognose; Wirtschaftsindikator; Prognoseverfahren; Europa